Migraine Pain Location and Measures of Healthcare Use and Distress: An Observational Study. (4th June 2018) - Loder, Elizabeth; Weizenbaum, Emma; Giddon, Donald
Abstract : Introduction . Lateralized pain is a core diagnostic feature of migraine. In previous research, left-sided spinal pain was more frequent and associated with greater emotional distress and healthcare use than right-sided pain. We hypothesized therefore that patients with left-sided head pain might experience higher levels of distress or healthcare use than those with right-sided or bilateral pain. Methods . Medical record information was extracted for 477 randomly selected patients with migraine seen in 2011 in a tertiary headache clinic. This included demographic data, pain location, handedness, comorbid psychiatric diagnoses, medical and emergency department visits, and use of selected headache medications. Results and Discussion . Two hundred twenty-eight of four hundred seventy-seven (47.8%) patients reported lateralized pain, of which 107 (47.9%) patients were right sided compared with 65 (28.5%) left-sided patients (p = 0.001 ), while 56 (24.5%) reported unilateral pain with no side predominance. Contrary to expectations, with the exception of self-reported posttraumatic stress disorder, there were no statistically significant differences between left and right in measures of psychiatric distress, emergency department visits, or healthcare use. Conclusion . Although unilateral pain location can be helpful in making a migraine diagnosis, it does not appear to have additional clinical implications. Additionally, its absence does not rule out a diagnosis of migraine since more than half of migraineurs have bilateral head pain.